BIOLOGICAL EFFECTS AND LEGAL ASPECTS WHILE PLACING BASIC MOBILE COMMUNICATION STATIONS IN RESIDENTIAL AREAS OF SETTLEMENTS - Biedunkova, Olha; Moroz, Oleksandr; Klуmenko Vladyslav (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The analysis of domestic standards for the placement of base stations of mobile communication systems in residential areas of settlements and the role of the public in making relevant decisions is carried out. Known studies of the effect of electromagnetic radiation on the health of people and experimental animals are considered. It was found that a long stay of living organisms in the zone of influence of base stations causes a number of negative biological effects. It is concluded that base stations should not be located directly within residential buildings, close to schools, healthcare facilities, parks and kindergartens.